COMPVID: estudo randomizado e controlado da inibição do complemento no tratamento da pneumonia por SARS-CoV-2 - Glauciene Prado Alves (2023)
Background: COVID-19 has a wide spectrum of clinical manifestations, and understanding the pathogenesis of the disease, especially in its severe and critical forms, is of fundamental importance for the study of possible therapeutic targets. Dysregulation of the complement system plays a central role in the evolution of patients with severe pneumonia associated with the SARS-CoV-2 virus. Objective: The present study aims to test the efficacy and safety of the medication Nomacopan, an inhibitor of complement C5 and leukotriene B4, in patients admitted with SARS-CoV-2 pneumonia at Hospital Eduardo de Menezes in Belo Horizonte, Minas Gerais, Brazil. Methods: A phase II, randomized, single-blind clinical case study was carried out, which included 24 patients hospitalized with SARS-CoV-2 pneumonia between 08/18/2020 to 10/24/2020 at Hospital Eduardo de Menezes. Data were prospectively collected from electronic hospital records and listed in tables. A descriptive analysis of the collected variables was performed and the groups were compared using the Mann Whitney test. Results: Of the 24 patients admitted to the study, 62.5% were male and 37.5% were female. The main comorbidity present was arterial hypertension (58.3%). There was no statistically significant difference between the severity of patients (News 2 score) when univariate analysis was performed between the two groups. Regarding the primary outcome, patients who received Nomacopan took longer to reach saturation >93% without O2, and this difference was statistically significant (p=0.001). This same group was also hospitalized longer (p=0.04) and had fewer oxygen-free days (p=0.001). The dosage of the final complement activity CH50 on D07 was not different between the groups, showing that the complement decreases on the third day of medication, but increases again on the seventh day. The medication appears to be safe and no drug-related side effects have been reported. Conclusion: Nomacopan was not effective in treating pneumonia caused by SARS-CoV-2 on the population of the study.